2023
DOI: 10.3389/fpubh.2023.1121860
|View full text |Cite
|
Sign up to set email alerts
|

Spatial network and driving factors of low-carbon patent applications in China from a public health perspective

Abstract: IntroductionThe natural disasters and climate anomalies caused by increasing global carbon emissions have seriously threatened public health. To solve increasingly serious environmental pollution problems, the Chinese government has committed itself to achieving the goals of peak carbon emissions and carbon neutrality. The low-carbon patent application is an important means to achieve these goals and promote public health.MethodsThis study analyzes the basic situation, spatial network, and influencing factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…With the release of the report Intellectual Property and the US Economy: Industries in Focus (ESA, 2012), the concepts of “patent density” and “patent‐intensive industries” has gradually entered the vision of scholars. From the perspective of research content, two main issues are concerned: Firstly is the definition of “patent‐intensive.” Scholars and policymakers have been updating the definition and criteria of “patent‐intensity” and refining the scope of PI industries, taking into account the actual situation of local technological innovation (de Rassenfosse & van Pottelsberghe de la Potterie, 2013); secondly, the research on innovation management regards the value orientation of patent intensity (Hu et al, 2023; Li et al, 2023; Lv et al, 2018).…”
Section: Literature Review and Theory Developmentmentioning
confidence: 99%
“…With the release of the report Intellectual Property and the US Economy: Industries in Focus (ESA, 2012), the concepts of “patent density” and “patent‐intensive industries” has gradually entered the vision of scholars. From the perspective of research content, two main issues are concerned: Firstly is the definition of “patent‐intensive.” Scholars and policymakers have been updating the definition and criteria of “patent‐intensity” and refining the scope of PI industries, taking into account the actual situation of local technological innovation (de Rassenfosse & van Pottelsberghe de la Potterie, 2013); secondly, the research on innovation management regards the value orientation of patent intensity (Hu et al, 2023; Li et al, 2023; Lv et al, 2018).…”
Section: Literature Review and Theory Developmentmentioning
confidence: 99%
“…Therefore, energy-consuming rights trading in the eastern region is more efficient, and the market incentive effect of the energy-consuming trading policy is more significant. On the other hand, the eastern regions tend to pay more attention to technological innovation and hold a better foundation for green innovation (Hu et al, 2023). Therefore, the eastern region has more advantages in technological innovation.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Tian et al (2021) conducted an investigation into the link between green bonds and several economic and environmental factors and came to the same conclusion. Hu et al (2023) found no link between green bonds and sustainable development goals (SDGs) in India due to a lack of rules in India's climate action plan and a financial gap in the private sector. Finally, Guo et al (2023) analyzed green bonds for renewable energy projects issued by the European Investment Banks in 2015-2018.…”
Section: Literature Reviewmentioning
confidence: 99%